EXPERIMENTAL CARDIOVASCULAR AND LUNG RESEARCHBiological effects of anti-CD34-coated ePTFE vascular grafts. Early in vivo experimental results - Mrówczyński, Wojciech; Rungatscher, Alessio; Buchegger, Franz; Tille, Jean-Christophe; Namy, Sophie; Ratib, Osman; Kutryk, Michael; Walpoth, Beat Hans (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Aim of the study: To assess the biological activity of anti-CD34 antibody-coated ePTFE vascular prostheses. Material and methods : Indium111-labeled autologous thrombocytes were administered to 5 anesthetized pigs after the placement of femoral arterial and venous catheters. An arterio-venous fistula, created by the random interposition of 4 different ePTFE grafts (A = dry control, B = dry anti-CD34, C = wet control, D = wet anti-CD34), was blood perfused for 0, 10, 30, 60 and 120 minutes. Radioactivity of each graft was measured and expressed in cpm/mg. Morphological studies were performed to assess intraluminal deposition. Results : The median radioactivity of graft B was significantly higher than that of graft A after 60 min (1074 vs. 18; p = 0.021) and 120 min (1990 vs. 25; p = 0.043) of perfusion. Similarly, graft D was significantly more active than graft C (60 min: 1388 vs. 26; p = 0.021 and 120 min: 2780 vs. 23; p = 0.021). Histological and SEM results confirmed the radio-labeling in-vivo studies by showing significantly more protein/cell and platelet depositions (p = 0.012). Conclusions: Anti-CD34-coated ePTFE grafts bound significantly more platelets/cells and proteins than their uncoated counterparts, confirming the bioactivity of the antibody. This process is time-dependent and matches the morphological results. The anti-CD34 coating may enhance temporal and spatial endothelialization of vascular grafts and, thus, possibly improve clinical results by providing direct endothelial progenitor cell (EPC) adhesion/entrapment or by creating a biocompatible protein-thrombocyte/cell layer that indirectly enhances migration and further proliferation of EPCs.